1987
DOI: 10.1302/0301-620x.69b1.3818721
|View full text |Cite
|
Sign up to set email alerts
|

Combined chemotherapy and surgery for hydatid bone disease

Abstract: Fig. 1 Life-cycle of the tapeworm Echinococcus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 13 publications
0
54
0
2
Order By: Relevance
“…Patients with extensive destruction of the ilium and hip (cases [6][7][8] These patients presented with pain in the hip, limitation of movement, and significant swelling around the hip with sinus formation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with extensive destruction of the ilium and hip (cases [6][7][8] These patients presented with pain in the hip, limitation of movement, and significant swelling around the hip with sinus formation.…”
Section: Resultsmentioning
confidence: 99%
“…Bone echinococcosis occurs in about 1-4% of patients who suffer from hydatid infestation [6], and the most commonly described sites are the vertebrae, the long bones of the lower limbs, the pelvis and hip joint, the ribs and the scapulae [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…b 3 years later, after surgery and 6 courses of albendazole therapy is better absorbed with higher levels of active metabolite in the cysts compared with other benzimidazoles [10]. The poorest response has, however, been in hydatid disease of bone, although Szypryt et al have reported 5 patients treated successfully by a combination of albendazole and surgery, even though only one or two cycles of chemotherapy were given [20]. Other studies have confirmed the effect of albendazole on hydatid disease which correlated with the duration of treatment [22].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment alone may not be successful because of the difficulty of total excision, and may increase the risk of dissemination. Recently a combination of chemotherapy with albendazole and operation has had encouraging results [20].…”
Section: Introductionmentioning
confidence: 99%